Experimental and numerical analysis of the cyclic behaviour of RC beam-column connections with plain reinforcing bars - Fernandes, C. (2013)
The information available in the literature about the cyclic behaviour of reinforced concrete elements with plain reinforcing bars is scarce. As a consequence, the influence of bar slippage in elements with plain bars is not yet comprehensively understood. In this paper are presented and discussed the main results of the cyclic tests carried out on five full-scale reinforced concrete beam-column joints with plain bars and without specific detailing for seismic demands. An additional joint specimen with deformed bars was also tested for comparison. Furthermore, numerical models were built to simulate the response of two of the specimens. Particular attention was given to the influence of bar slippage. The results of the conducted analyses underline the importance of accounting for bond-slip in the numerical modelling of elements with plain bars and also highlight the need for specific models to simulate the effects of this mechanism in the presence of plain bars.